A family‐based genetic study identifies mutations in TLR9 impairing receptor activation: A role for innate immunity in AD pathogenesis: Developing topics. (7th December 2020) - Cacace, Rita; Hoogmartens, Julie; Hens, Elisabeth; Buist, Arjan; Cras, Patrick; Sieben, Anne; Vandenberghe, Rik; Engelborghs, Sebastiaan; De Deyn, Peter Paul; Martin, Jean‐Jacques; Moechars, Diederik; Van Broeckhoven, Christine; et al.
Abstract: Background: Family‐based genetic studies in early‐onset Alzheimer disease (EOAD), prompting early gene discoveries, remain powerful for the identification of novel genes in AD. Causal mutations in APP, PSEN1 and PSEN2 explained <10% of EOAD patients, while several EOAD families remained genetically unexplained. We identified a multigenerational Flanders‐Belgian family with autosomal dominant EOAD. DNA, biomaterials and clinical data from two consecutive informative generations were available: 5 AD patients (onset 64.2±13.2 years, range 52‐85) of which 2 with a definite neuropathological diagnosis and 9 unaffected/at‐risk individuals. Method: Whole exome sequencing of 4 patients. Selection of shared rare non‐synonymous variants, validation of co‐segregation with disease and variants frequency assessment using massive parallel‐targeted sequencings (MPS). We used genotyping of STR markers to define haplotypes. Coding regions of candidate genes were sequenced using MPS in a Belgian cohort of 320 EOAD (onset 57.8±5.9y, range 33‐65) and 1166 late‐onset (LO)AD (onset 77.1±6.5y, range 66‐96) patients and a control cohort of 934 persons (inclusion 70.45±9.2y, range 52‐100). Variants pathogenicity was predicted using CADD scores cutoff>20. Evaluation of functional effects by NF‐κB luciferase assay. Result: Three rare variants co‐segregated with AD in the family: CCR3 p.F249Hfs*23 (rs561062190), ZNF589 p.T355M (rs376706270) and TLR9 p.E317D (novel) and are located within a co‐segregating haplotype block of 15.3 cM at ch3p21. Only the TLR9 variant was absent in controls. TLR9 is a DNA‐sensing receptor expressed in immune cells, recognizes unmethylated CpG oligonucleodides and is responsible for innate immune cells activation and mounting acquired responses. The NF‐κB luciferase assay showed that p.E317D, located within the ligand sensor pocket of TLR9, caused a 50% reduction in receptor activation. TLR9 resequencing identified additional rare variants carriers: 7 in EOAD (7/320, 2.19%) and 19 in LOAD (19/1166, 1.63%) patients and 8 in controls (8/934, 0.86%), while TLR9 p.E317D was absent. Of the rare variants, 16 were in patient‐only, 3 in patients and controls and 5 in controls‐only. The NF‐κB luciferase assay indicated reduced TLR9 activation for the novel variants specific to EOAD patients and with a CADD score >20. Conclusion: We discovered TLR9 as candidate gene in AD with a mechanism of loss of receptor activation.